2020
DOI: 10.1098/rspb.2020.2561
|View full text |Cite
|
Sign up to set email alerts
|

A single heat-stress bout induces rapid and prolonged heat acclimation in the California mussel,Mytilus californianus

Abstract: Climate change is not only causing steady increases in average global temperatures but also increasing the frequency with which extreme heating events occur. These extreme events may be pivotal in determining the ability of organisms to persist in their current habitats. Thus, it is important to understand how quickly an organism's heat tolerance can be gained and lost relative to the frequency with which extreme heating events occur in the field. We show that the California mussel, Mytilus califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Both congeners are likely to experience temperatures in these ranges in the field, so the costs of maintaining haemocyte populations and, by extension, populations of other types of cells as well could be substantial components of sublethal thermal stress. Note that cardiac critical temperatures for M. californianus are always above 32 C, regardless of latitude (Logan, Kost & Somero, 2012) or vertical position (Moyen et al, 2019) of the sampled populations. Thus, considerable amounts of thermal damage at the cellular level may ensue before an organ-level property like cardiac critical temperature manifests during thermal stress.…”
Section: Adaptive Variation In Thermal Responses Of Intertidal Mollus...mentioning
confidence: 93%
See 2 more Smart Citations
“…Both congeners are likely to experience temperatures in these ranges in the field, so the costs of maintaining haemocyte populations and, by extension, populations of other types of cells as well could be substantial components of sublethal thermal stress. Note that cardiac critical temperatures for M. californianus are always above 32 C, regardless of latitude (Logan, Kost & Somero, 2012) or vertical position (Moyen et al, 2019) of the sampled populations. Thus, considerable amounts of thermal damage at the cellular level may ensue before an organ-level property like cardiac critical temperature manifests during thermal stress.…”
Section: Adaptive Variation In Thermal Responses Of Intertidal Mollus...mentioning
confidence: 93%
“…one important consideration to incorporate into experimental design. For example, Moyen et al (2019) showed that the rate of heating (in air) in a laboratory setting could lead to significant variation in critical temperature of cardiac function in M. californianus. Specimens from low and high intertidal sites differed in their responses; only high-site individuals exhibited changes in critical temperature with heating rate.…”
Section: Adaptive Variation In Thermal Responses Of Intertidal Mollus...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this prism, Connor and Gracey 75 reported that M. californianus exhibits phenotypic plasticity with respect to transcriptomic expression during cycles of aerial exposure and that it may produce a type of “heat hardening”, thus promoting homeostasis in the intertidal environment and enhanced tolerance to low-tide heating events. Moyen et al 34 recently reported that this adaptive strategy via phenotypic plasticity will likely prove beneficial for M. californianus and other mussel species under the extreme heat events projected with progressing climate change.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the expression pattern and thresholds of the transcriptional induction of stress response genes during heat hardening play an important role in development of the heat-tolerant phenotypes of animals 29 33 . Such phenotypic plasticity in response to heat hardening have been proposed as an adaptive strategy under the extreme heat events predicted with climate change for marine mussels including Mytilus californianus (Conrad, 1837) 34 . However, the physiological and molecular mechanisms of heat hardening are not well understood in marine ectotherms, including mussels, and require further investigation to assess the potential mechanisms underlying the organism’ ability to cope with extreme weather events such as marine heat waves.…”
Section: Introductionmentioning
confidence: 99%